Role of AMRUT Project in Urban Governance of West Bengal: A Review of Barddhaman Municipality (2015-2020) - Sayan Kumar Roy (Khazanah Sosial, 2023)
The term "urban governance" refers to the effective planning, financing, and reforms in the delivery of urban services to people. Deficits in India's urban basic infrastructure pose a threat to inclusive governance. As a result, schemes such as AMRUT have been developed to fill infrastructure gaps and improve service delivery through effective planning, financing, decentralized-digital reforms, and people's participation. This paper will critically investigate the underlying process that projects like AMRUT use to develop urban planning, financing, reforms, and services more accountable, effective, transparent, and inclusive.